Explicit corrective feedback and gestures in pronunciation instruction: Effects on Egyptian ESL learners' oral accuracy - El Kholy, Omnia Fouad (AUC Knowledge Fountain, 2018)
The present study investigated the effectiveness of using explicit corrective feedback (CF) and gestures in pronunciation instruction on the accuracy of both the interdental fricatives (voiced and voiceless) sounds: /θ/ pronounced as /s/, /ð/ pronounced as /z/, and the bilabial stop /p/ pronounced as /b/, which are problematic for Egyptian adult ESL learners. The study investigated the pronunciation of 47 male and female adult non-native speakers of English between the ages of 18 and 35 learning English in the general English program of a private institution affiliated with one of the major universities in Egypt. The students were recruited based on their proficiency level which was within the range of intermediate to advanced, i.e. A2/B1 on the Common European Frame of Reference, based on their placement test scores. All participants were evaluated by three volunteer raters who were experienced teachers of English as a second language and MA TESOL holders. The participants were divided into two groups: a treatment group (27 participants) and a control group (20 participants) and were assessed based on pre- and post-performance assessments in the form of a matched guise procedure by the three raters. The researcher used one instrument in collecting the data: pre- and post-performance assessments in the form of a matched guise procedure for both the treatment and the control group. To illustrate, each participant was (1) asked to insert a picture in a given frame showing a word that has one of the target sounds, and (2) read a scripted monologue during the first session of the semester before any pronunciation instruction. After the treatment interventions, each participant was given different pictures to insert in a frame – as mentioned above – and a different scripted monologue to read during session 12. A four-stage experiment: (1) presentation/recording, (2) listening to the recording/corrective feedback (explicit CF for the treatment group/recasts for the control group) and modeling the target sounds, (3) practicing, recalling and recognizing the target sounds, and (4) presentation/recording, was conducted on the two groups (treatment and control) to study the effectiveness of using explicit corrective feedback (CF) and gestures in pronunciation teaching of the target problematic sounds (/θ/, /ð/, /p/) of Egyptian ESL learners over methods like repetition and recast of the target problematic sounds. The raters were then given the recordings of the same participants pre- and post- performance, without knowing that these recordings were for the same learners – and their task was to evaluate these voices based on a frequency count scale to quantify the degree of accuracy of the target sounds and fill in a commentary on the participants’ pre- and post- recordings to qualitatively assess their overall comprehensibility in connected speech and to compare the differences between the natural speech post-test and the scripted monologue post-test. The scores for both groups were compared using T-tests to check for significant improvement in specific pronunciation features. The results of the study showed a significant improvement in the pronunciation accuracy and overall comprehensibility of the participants in the treatment group who were exposed to explicit corrective feedback and gestures in pronunciation instruction as compared to the participants in the control group whose pronunciation proficiency did not show significant improvement. This study presents a number of pedagogical implications and contributions as it supports the use of explicit corrective feedback and gestures in the classroom, and it highlights directions that could be targeted for further research.